AN ATTENTIVE READER - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
M Baumer, Montpellier, France: 'I have noticed a mistake on page 11 of the French edition of Spore 59. The picture on the left is not Atriplex but Opuntia and probably Opuntia ficus-indica.'